A tale of two MENAs: Food Security in the Middle East and North Africa - Khouri, Nadim (2018)
Launch of the IFPRI 2018 Global Food Policy Report: Food Security from Global to MENA Beirut, Lebanon Co-Organized by IFPRI, the Faculty of Agricultural and Food Sciences (FAFS) and the Food Security Program at the American University of Beirut